DIAGNOSTIC ACCURACY OF COMPUTED TOMOGRAPHY CHEST FOR DIAGNOSIS OF ANEMIA TAKING COMPLETE BLOOD COUNT AS GOLD STANDARD (The Research of Medical Science Review, 2025)
Introduction: Low hemoglobin levels as indicated by anemia are prevalent in millions of people especially those in areas with limited health-care access. CBC remains the most gold standard in approaching anemia but chest CT scans as an imaging technique can also be beneficial as they detect anemia- and related findings. Objective: To evaluate the diagnostic accuracy of unenhanced chest CT in detecting anemia, using CBC as the gold standard, in a Pakistani hospital setting. Materials and Method: The present study is a cross-sectional descriptive study that was carried out at the National Medical Centre, Karachi, between January and December 2023. Readers included 257 patients aged between 18 and 65 years with CCT and CBC. Hemorrhagic signs, hyperdense aortic signs and low left ventricular cavity attenuation, were compared to consent with CBC anemia defined as hemoglobin <12 g/dL for women and <13 g/dL for men. Results: The prevalence rate of anemia in participants of this study was 82.1 percent, of whom 35.8 percent had moderate anemia. This study reveals that CT possesses moderate sensitivity and specificity, although anemia occurrence was observed to differ significantly between genders.Conclusion: Unenhanced chest CT offers potential as an adjunct for anemia detection, particularly in settings with limited laboratory access. Targeted interventions are needed to address the high anemia burden, especially among females.